2002
DOI: 10.1051/animres:2002040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maturity stage and chopping length of maize silage on particle size reduction in dairy cows

Abstract: -The effects of maturity stage and chopping length of maize silage on chewing behaviour, particle size reduction and rumen retention time were studied in four lactating cows fitted with a ruminal cannula, according to a 4 × 4 Latin square design. Maize silage made up 80% of the diet and the cows were fed at 90% of the ad libitum intake level. Chopping length had only a significant effect on the particle size of the maize harvested at the late maturity stage. For the latter, the proportion of particles larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…The FG conditioning simulated soaked chewed particles during ingestion (Fernandez and Michalet-Doreau, 2002) but failed to take into account the essential chewing during rumination that reduces particle size to facilitate aNDF degradability by microbial enzymes (Beauchemin and Yang, 2005). Contrary to D1 and D4, the coarse grinding of the FG conditioning is likely insufficient to make aNDF accessible to microbial enzymes, which would explain the lower aNDF degradation of FG samples.…”
Section: Effect Of the Sample Conditioning Methods On Degradation In Tmentioning
confidence: 99%
“…The FG conditioning simulated soaked chewed particles during ingestion (Fernandez and Michalet-Doreau, 2002) but failed to take into account the essential chewing during rumination that reduces particle size to facilitate aNDF degradability by microbial enzymes (Beauchemin and Yang, 2005). Contrary to D1 and D4, the coarse grinding of the FG conditioning is likely insufficient to make aNDF accessible to microbial enzymes, which would explain the lower aNDF degradation of FG samples.…”
Section: Effect Of the Sample Conditioning Methods On Degradation In Tmentioning
confidence: 99%
“…In addition, long particles are reduced in size during ingestive mastication, thereby eliminating the effects of particle length. Fernandez and Michalet-Doreau (2002) reported that mean particle length markedly decreased after ingestive mastication, and the decrease was greater for coarsely chopped than for finely chopped CS. Fermentability of concentrate could be another factor influencing digestion.…”
Section: Intake Digestibility and Microbial Productionmentioning
confidence: 98%
“…At the same time, DMI decreased by 3.3 kg/d, indicating that it took the cows longer to consume less DM of more coarsely chopped silage. Similarly, Fernandez and Michalet-Doreau (2002) compared corn silage chopped to either 4.2 or 12.0 mm theoretical length of cut and observed that time spent eating was reduced by 43 min/d for cows fed the finer chopped silage despite similar DMI. Fernandez et al (2004) compared the effects of 2 corn silage hybrids varying in NDF digestibility either when finely or coarsely chopped (5 vs. 13 mm theoretical length of cut, respectively).…”
Section: Silage Fiber Characteristics Feeding Behavior and Dmimentioning
confidence: 99%